L. C. Stambaugh correspondence - Stambaugh, L. C.
Photocopy of a letter from Stambaugh to John McSparren relating to a postal appointment and local politics in Lancaster, Pa.
Negative photocopy produced with the permission of Isabella McSparren.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: McSparren, John -- Correspondence; Postal service -- Pennsylvania; Lancaster (Pa.) -- Politics and government; Lancaster (Pa.) -- History